Managers' attitudes to creativity and innovation practices in the creative industries - Sousa, Fernando (2019)
This article aims to demonstrate that the relationship between entrepreneurs' attitudes to creativity and business innovation practices is stronger in the case of creative industries. A sample of 454 managers of micro and medium-sized companies (94 belonging to creative industries) was surveyed using an inventory of innovative business practices and the scale of attitudes towards creativity. The results, derived from a linear regression model (two factors for the scale of attitudes - Leadership and Autonomy - and for the inventory of business practices - Performance and Strategy), confirmed the proposition by revealing the influence of the creative attitudes of managers regarding the company's innovative practices, fundamentally on Strategy, especially in the creative industries segment. The innovative manager appeared as a disciplined individual driven to collaborating with the employees. Although this research requires further evidence, the results suggest interesting characterisations of the managers who develop their activity in the cluster of creative industries.